A Study of the Static Durability of the Valve Closure Component Using Materials Resistance Methods and Flexibility Theory - اسبر منى; نصرة عواطف (Latakia University Journal -Engineering Sciences Series, 2020)
This work aims to find approximate relationships to calculate the static durability of ball valve disc valves, based on material resistance and flexibility theory. Three groups were obtained, and these groups represent three mathematical charts, each of which corresponds to specific relationships obtained to calculate the stresses generated in the dish.